Optimization of Data Encryption Technology in Computer Network Communication - Lin, Jun; Shen, Zhiqi (International Journal for Applied Information Management, 2023)
In recent years, the pervasive integration of computer network communication systems across various industrial domains has revolutionized daily life and work, offering unprecedented convenience. Recognizing the paramount importance of securing these communication channels, this paper meticulously examines the current landscape and distinctive features of data encryption technology in computer network communication security. To comprehend the evolving threat landscape, the paper elucidates prevalent security challenges confronting contemporary networks. Subsequently, the study delves into a comprehensive discussion on the implementation of data encryption technology to fortify network communication security. This includes a nuanced exploration of link encryption technology, node encryption technology, and end-to-end encryption technology, elucidating their respective roles and effectiveness. Moreover, the paper undertakes a profound analysis of the practical application of data encryption technology within the realm of computer network communication security. Employing empirical evidence, the study reveals significant findings, such as the Mean Squared Error (MSE) values for data sets. Specifically, the MSE value for data 1 is recorded at 42.453, data 2 at 87.324, and data 3 at 87.324674. These findings provide invaluable insights into the performance and efficacy of data encryption technology in safeguarding computer network communications, paving the way for enhanced security measures in the dynamic and ever-expanding digital landscape.